Internet use, cardiometabolic multimorbidity, and death in older adults: a multi-cohort study spanning developing and developed countries - Ziyang Ren; Shuangbo Xia; Jinfang Sun; Duoduo Wang; Yushan Du; Ning Li; Jufen Liu (BMC, 2023)
Abstract Background Internet use is a double-edged sword for older adults' health. Whether internet use can prevent cardiometabolic diseases and death in older adults remains controversial. Methods Four cohorts across China, Mexico, the United States, and Europe were utilized. Internet use was defined using similar questions. Cardiometabolic diseases included diabetes, heart diseases, and stroke, with 2 or more denoting cardiometabolic multimorbidity. Depressive symptoms were assessed using the Center for Epidemiological Studies Depression Scale and Europe-depression scale. The competing risk analysis based on subdistribution hazard regression, random-effects meta-analysis, and mediation analysis were utilized. Results A total of 104,422 older adults aged 50 or older were included. Internet users (vs. digital exclusion) were at lower risks of diabetes, stroke, and death, with pooled sHRs (95% CIs) of 0.83 (0.74-0.93), 0.81 (0.71-0.92), and 0.67 (0.52-0.86), respectively, which remained significant in sensitivity analyses. The inverse associations of internet use with new-onset cardiometabolic diseases and death were progressively significant in Mexico, China, the United States, and Europe. For instance, older internet users in Europe were at 14-30% lower cardiometabolic risks and 40% lower risk of death. These associations were partially mediated by reduced depressive symptoms and were more pronounced in those with high socioeconomic status and women. Furthermore, patients with prior cardiometabolic conditions were at about 30% lower risk of death if they used the internet, which was also mediated by reduced depressive symptoms. However, certain cardiometabolic hazards of internet use in those aged < 65 years, with low socioeconomic status, men, and single ones were also observed. Conclusion Enhancing internet usage in older adults can reduce depressive symptoms and thus reduce the risks of cardiometabolic diseases and death. The balance of internet use, socioeconomic status, and health literacy should be considered when popularizing the internet in older adults.